An international audit of the management of dyslipidaemia and hypertension in patients with rheumatoid arthritis: results from 19 countries. Issue 6 (7th July 2021) - Rollefstad, Silvia; Ikdahl, Eirik; Wibetoe, Grunde; Sexton, Joe; Crowson, Cynthia S; van Riel, Piet; Kitas, George D; Graham, Ian; Dahlqvist, Solbritt Rantapää; Karpouzas, George; Myasoedova, Elena; Gonzalez-Gay, Miguel A; et al.
Abstract: Aims: To assess differences in estimated cardiovascular disease (CVD) risk among rheumatoid arthritis (RA) patients from different world regions and to evaluate the management and goal attainment of lipids and blood pressure (BP). Methods and results: The survey of CVD risk factors in patients with RA was conducted in 14 503 patients from 19 countries during 2014–19. The treatment goal for BP was <140/90 mmHg. CVD risk prediction and lipid goals were according to the 2016 European guidelines. Overall, 21% had a very high estimated risk of CVD, ranging from 5% in Mexico, 15% in Asia, 19% in Northern Europe, to 31% in Central and Eastern Europe and 30% in North America. Of the 52% with indication for lipid-lowering treatment (LLT), 44% were using LLT. The lipid goal attainment was 45% and 18% in the high and very high risk groups, respectively. Use of statins in monotherapy was 24%, while 1% used statins in combination with other LLT. Sixty-two per cent had hypertension and approximately half of these patients were at BP goal. The majority of the patients used antihypertensive treatment in monotherapy (24%), while 10% and 5% as a two- or three-drug combination. Conclusion: We revealed considerable geographical differences in estimated CVD risk and preventive treatment. Low goal attainment for LLT was observed, and only half the patients obtained BP goal. Despite a high focus on the increased CVD risk in RA patients over the last decade, there is still substantial potential for improvement in CVD preventive measures.